Discovering Real Time Travel Package Recommendation Using Collaborative Tagging - , M.Suresh kumar, F.Anishya, (International Journal of Scientific Research and Management (IJSRM), 2015)
Now a days internet has become insolubly linked to people, in the world of peregrination, enjoyment more and more travel firm supplies online utility by using tourist area season topic model which only use individual trait along the travel statistics and it fails to provide a customized package for customers. Hence a tourist relational area season topic model is enhanced, which provides automatic travel group formation and it has the capability to find the neighboring places apart from the user search and thereby it provides efficacious information for creating the packages. To perform this operation N-Way Search Algorithm is used. As the solution which is more efficient than the conventional recommend system and also satisfies the user by providing recommend package. It follows the hybrid recommendation strategy to produce efficient results to the travellers and collaborative tagging which mainly works in tagging the neighboring places and predicting the value for the recommended areas, this mechanism helps to capture effective results in the real world recommender system.